Toxicity profiling and antioxidant activity of ethyl acetate extract of leaves of Premna integrifolia L. for its application as protective agent against xenobiotics. (2021) - Singh, Chandrashekhar; Tiwari, Kavindra Nath; Kumar, Pradeep; Kumar, Anil; Dixit, Jyoti; Saini, Rajesh; Mishra, Sunil Kumar
Graphical abstract: Abstract: Premna integrifolia L. (Lamiaceae) is widely used in herbal formulation "Dashmoolarishta" which is useful in postnatal care. Ethyl acetate extract obtained from the leaves was evaluated for phenolic content and its antioxidant activity. Acute and subacute toxicity of the extract was studied in mice of both sexes to get an idea about LD50 value and assessed its safety profile before its application as a protective agent against different toxicities induced by xenobiotics. Phenol enriched extract (phenol content is 63.10 ± 1.26 mg/g of gallic acid equivalent and flavonoid content 75.33 ± 0.23 mg/g of rutin equivalent) showed good antioxidant activity. In acute toxicity studies it was observed that single different doses (300−5000 mg/kg b.wt.) of extract did not show any mortality of mice. Thus the LD50 of the extract was determined, and it was higher than 5000 mg/kg. There was no major change in behavioral and general appearance of mice. External morphology of liver, kidneys, lungs, spleen and heart did not show any effect of treatment. In subacute toxicity no statistically significant change in body weight, relative organ weight, food intake and water uptake, hematological, biochemical parameters were reported after comparison with control. Extract did not show significant effect in the level of antioxidant enzymes in the liver of mice of treated groups. No histopathological changes were observed in liver and kidney tissues. Thus, extract did not show any sign of toxic effects, when administered orally to male and female mice at dose level up to 1000 mg/kg. So, it can be utilized as protective agent against toxicity produced by different xenobiotics.